Water‐driven shape memory nanocomposite fibers for actuators - Wang, Changchun; Wang, Lei; Zhang, Zewu; Zhang, Na; Huang, Yu‐an (Polymer composites, 2023)
Shape memory polymer (SMP) can store entropic energy during programming and release the energy as recovery. The released energy is determined by the recovery strain and the recovery stress. The low recovery stress of SMP limits its application. In this paper, shape memory nanocomposite fibers (SMNFs) prepared by wet spinning through a two‐step orientating process show thermo‐active and water‐driven shape memory effect. Carbon nanotubes (CNTs) are uniformly dispersed in SMNF and aligned along the SMNF axis. SMNF with 13 wt% CNT has an average maximum recovery stress of ~160 MPa at 100°C, which is almost five times higher than that of a pure PVA fiber. The uniform distribution of the orientational CNTs in the SMNFs and the confinement effect of the CNTs confirmed by the increased relaxation time contribute to the increment of the recovery stress. Aligned CNTs impede the mobility of amorphous chains and increase the Tg of SMNFs. The twisted SMNF can drive an object up to 25 times its own weight in water to rotate and lift. The rotational velocity of the twisted SMNF is sensitive to temperature. Water molecules acting as plasticizers greatly enhance the mobility of the PVA chains, and the SMNF in water releases the stored entropic energy at room temperature. The SMNF with high recovery stress demonstrates its potential for applications in the field of actuators and artificial muscles. Shape memory nanocomposite fibers (SMNFs) prepared by wet spinning through a modified two‐step orientating process. The twisted SMNF with 13 wt% CNT can drive an object up to 25 times its own weight in water to rotate and lift.